CONTACT GENERATION AND CONVERSION OF EXCHANGE INERTIAL RADIATION BY ROTATIONAL TOPOLOGICAL DISCONTINUITIES IN COMPLEX SPACE UNDER CONDITIONS OF Q-FACTOR MODULATION, TUNNELING AND STRONG INTERACTION: COLD BUFFETING VERSUS WARM FREE GENERATION - ZASPA, YURII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The contact generation of exchange inertial radiation by rotational topological discontinuities of complex space in nonequilibrium open natural systems is investigated. The physical mechanisms of the strong interaction in the combination of two fundamental fields - electromagnetic and gravitomagnetic - are established, and the conditions for its dominance over electrostatic and gravitostatic interactions are determined. Two significantly different modes of exchange inertial radiation generation are revealed: low-temperature buffeting with exchange-tunnel modulation of the Q-factor of the near-discontinuity resonator and high-temperature free generation. Examples of such modes in the dynamics of natural systems of different levels and scales of organization are given. The turbulent transformation and thermalization of jet and vortex-like motion structures formed by buffeting, which are associated with the loss of their coherence, are investigated. Relevant examples in technical, space, and pseudo-elementary systems are given. The main role of this kind of processes in the dynamic thermoregulation of the Earth’s climate, which is erroneously attributed to the anthropogenic factor in the noisy concepts of modern global warming, is noted. The mechanisms of formation of the rest mass, charge, spin and magnetic moment of microparticles are established. The relativistic principle of equivalence of inert and gravitational masses is refuted and the discrepancy between modern physical standards in the field of fundamental interactions (SM) and cosmology (Lambda-CDM) and natural data on symmetry, topology, energy, dynamics and evolution of non-equilibrium open systems is revealed.